AQP4 Antibody Assay Sensitivity Comparison in the Era of the 2015 Diagnostic Criteria for NMOSD - Prain, Kerri; Woodhall, Mark; Vincent, Angela; Ramanathan, Sudarshini; Barnett, Michael H.; Bundell, Christine S.; Parratt, John D. E.; Silvestrini, Roger A.; Bukhari, Wajih; , The Australian and New Zealand NMO Collaboration; Brilot, Fabienne; Waters, Patrick; et al. (Frontiers in Neurology, 2019)
We have compared 5 different assays for antibodies to aquaporin-4 in 181 cases of suspected NMOSD and 253 controls to assess their relative utility. As part of a clinically-based survey of NMOSD in Australia and New Zealand, cases of suspected NMOSD were referred from 23 centers. Clinical details and magnetic imaging were reviewed and used to apply the 2015 IPND diagnostic criteria. In addition, 101 age- and sex-matched patients with multiple sclerosis were referred. Other inflammatory disease (n=49) and healthy controls (n=103) were also recruited. Samples from all participants were tested using tissue-based indirect immunofluorescence assays and a subset were tested using four additional ELISA and cell-based assays. Antibodies to myelin oligodendrocyte glycoprotein were also assayed. All aquaporin-4 antibody assays proved to be highly specific. Sensitivities ranged from 60 – 94%, with cell-based assays having the highest sensitivity. Antibodies to myelin oligodendrocyte glycoprotein were detected in 8/79 (10%) of the residual suspected cases of NMOSD. Under the 2015 IPND diagnostic criteria for NMOSD, cell-based assays for aquaporin-4 are sensitive and highly specific, performing better than tissue-based and ELISA assays. A fixed cell-based assay showed near-identical results to a live-cell based assay. Antibodies to myelin oligodendrocyte glycoprotein account for only a small number of suspected cases.